Numerical Analysis on Thermal Comfort in Rooms Using Convective Heating and Radiant Heating Terminals - Vizitiu Ștefănica-Eliza; Burlacu Andrei; Vizitiu Robert Ștefan (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section)
The concept of energy is closely related to the building sector and the systems used for heating, implicitly energy saving which is a current problem of both old and new buildings. In this paper a series of numerical simulations were made in Autodesk CFD Simulation in order to study the influence of terminal heating systems over the thermal comfort in rooms. Three case solutions were analysed, as follows: heating a room using a steel radiator, heating a room using an aluminium radiator and heating a room using underfloor heating. The values resulted through numerical simulations for the average room temperature were compared with the values for ideal heating. It was observed that underfloor heating is the most efficient source of heating among those analysed. Compared to heating using radiators, the temperatures along the length and height of the room using underfloor heating are constant and close to the ideal heating. The human body feels the most comfortable due to the uniform distribution of temperature from ground level, on height.